Riqueza e impuestos: el nacimiento de la Hacienda Pública en Yucatán (1821-1825) - Moreno Acevedo, Elda (2014)
Focusing on the process of state formation and the development of the national treasury in newly independent Mexico, this article examines how the province of Yucatan transitioned to a new tax structure between 1821 and 1825. The article pays particular attention to strategies that local institutions undertook to generate revenue and implement the new tax system in light of the historical lack of wealth in the region.